Decoding dynamic Ca2+ signaling in the vascular endothelium - Taylor, Mark S.; Francis, Michael (Frontiers in Physiology, 2014)
Although acute and chronic vasoregulation is inherently driven by endothelial Ca2+, control and targeting of Ca2+-dependent signals are poorly understood. Recent studies have revealed localized and dynamic endothelial Ca2+ events comprising an intricate signaling network along the vascular intima. Discrete Ca2+ transients emerging from both internal stores and plasmalemmal cation channels couple to specific membrane K+ channels, promoting endothelial hyperpolarization and vasodilation. The spatiotemporal tuning of these signals, rather than global Ca2+ elevation, appear to direct endothelial functions under physiologic conditions. In fact, altered patterns of dynamic Ca2+ signaling may underlie essential endothelial dysfunction in a variety of cardiovascular diseases. Advances in imaging approaches and analyses in recent years have allowed for detailed detection, quantification, and evaluation of Ca2+ dynamics in intact endothelium. Here, we discuss recent insights into these signals, including their sources of origination and their functional encoding. We also address key aspects of data acquisition and interpretation, including broad applications of automated high-content analysis.